Baseline Specimens of Erosion and Abrasion Studies - Ishak, Hayati; Field, James; German, Matthew (European Journal of Dentistry, 2020)
The difficulty in obtaining human teeth that are caries-free that have similar environmental exposure, e.g., diet intake and water fluoridation has lead researchers to opt for bovine teeth as a substitute for erosion studies. Bovine mandibular incisors are readily available at abattoirs and often originate from the same region and are likely to consume similar dietary intake. The bovine teeth for erosion or abrasion studies usually undergo specimen preparation to produce a “flat surface” baseline specimen. Among other terms used to define baseline specimens for erosion and abrasion studies include phrases like “optically flat” and “flat and smooth surface.” However, these terms might have no quantitative value as it does not justify the actual surface characteristics of the prepared flattened surface. In dentistry, roughness average (Ra) is the most commonly used parameter when reporting the roughness of specimens Reporting Ra alone might not be sufficient as it does not provide information regarding the surface texture as there is no distinction between valleys and peaks, nor does it provide information about the core structure of a material unlike the bearing area curve. The incorporation of Ra and BAP values in baseline specimens has the potential in predicting the wear or lubricating potential of these specimens. Furthermore, standardization of baseline specimens by acknowledging its surface roughness values ensures comparability of erosion and abrasion studies as different specimen preparation technique might influence the outcome or results of research.
Keywords: bearing area parameters; enamel; silicon carbide abrasive papers; surface roughness